Development of an Augmented Reality-Based History Learning Model to Improve Historical Literacy Among Secondary School Students - Kurniawan, Rudi; Haminangan, Ryan; Avin Maulana, M.; Gunawan Romadon, Haris (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to develop a pedagogically validated Augmented Reality (AR)-based history learning model to enhance secondary school students' historical literacy, motivation, and engagement. This study addresses the pressing issue of low historical literacy, often exacerbated by conventional teaching methods perceived as monotonous and irrelevant. Method: This study employed a tailored Research and Development (R&D) approach adapted from the Borg and Gall model, encompassing three main phases: needs identification, development, and evaluation. Comprehensive data were collected from 30 students, teachers, and experts through surveys, interviews, observations, and historical literacy tests (pre- and post-tests). Results: The developed AR prototype successfully integrated 3D visualizations, interactive narratives, and gamified quizzes to create an immersive learning experience. The model's implementation yielded substantial improvement: the students’ average historical literacy score increased significantly by 22.4% (from 55.0% to 77.4%); furthermore, the model demonstrated high user acceptance, with a student satisfaction rate of 84%. Expert validation further affirmed the model’s pedagogical soundness, content accuracy, and curriculum alignment. Novelty: This study introduces an integrated AR framework explicitly designed for Indonesian history education, effectively transforming traditional instruction into an interactive and contextual experience. This approach supports Sustainable Development Goal 4 (SDG 4) objectives by promoting innovative and equitable access to quality education.